A preliminary study of the relationship between working memory, language experience, and grammatical skill in dual language learners. (December 2021) - Jenkins, Kimberly C; Anderson, Raquel T
Purpose: This study examined the relationship between verbal short-term and working memory, language experience, and English tense-marking skill in Spanish L1-English L2 dual language learners (DLLs). Methodology: Ten Spanish-English DLLs, in kindergarten and first grade, participated in the study. Children completed the Test of Early Grammatical Impairment, a narrative retell task in English, and verbal memory tasks. Parents provided information regarding language input and output in the home and school environment. Data and analysis: Correlational analyses were conducted to examine relationships between English and Spanish input/output, forward and backward digit span, assessed in English and Spanish, and the accurate and productive use of English tense morphemes in various linguistic contexts. Conclusions: Study outcomes indicated varied use of English tense morphemes among DLLs. Additionally, a strong, positive association was found between the use of a variety of distinct tense forms and verbal working memory performance. Originality: This study is the first investigation to examine verbal short-term and working memory and home language experience to advance our understanding of the specific child internal and external factors that may account for the variability in tense marking during English second language acquisition. Significance: This research provides further insight to the effects of individual differences on the acquisition of second language grammatical skill during childhood.